Adjuvant HPV vaccination for anal cancer prevention in HIV-positive men who have sex with men: The time is now. Issue 38 (12th September 2017) - Deshmukh, Ashish A.; Cantor, Scott B.; Fenwick, Elisabeth; Chiao, Elizabeth Y.; Nyitray, Alan G.; Stier, Elizabeth A.; Goldstone, Stephen E.; Wilkin, Timothy; Chhatwal, Jagpreet
Highlights: We examined value of adoption of adjuvant qHPV vaccine for anal cancer prevention. We performed cost-effectiveness and value of information analysis. HPV vaccination is cost-effective for managing HIV-positive MSM with HSIL. Future clinical research data will not change this policy conclusion. Implementing adjuvant HPV vaccination soon will provide excellent value for money. Abstract: Importance: Outcomes of treating high-grade squamous intraepithelial lesions (HSIL), a precursor to anal cancer, remain uncertain. Emerging evidence shows that post HSIL treatment adjuvant quadrivalent human papillomavirus (qHPV) vaccination improves the effectiveness of treatment. However, no recommendations exist regarding the use of qHPV vaccine as an adjuvant form of therapy. Our objective was to determine whether post-treatment adjuvant vaccination should be adopted in HIV-infected MSM (individuals at highest risk for anal cancer) on the basis of cost-effectiveness determined using existing evidence or whether future research is needed. Methods: We developed a Markov (state-transition) cohort model to assess the cost-effectiveness of post-treatment adjuvant HPV vaccination of 27 years or older HIV-infected MSM. We first estimated cost-effectiveness and then performed value-of-information (VOI) analysis to determine whether future research is required by estimating the expected value of perfect information (EVPI). We also estimated expected value of partial perfect information (EVPPI) to determine what new evidences should have highest priority. Results: With the incremental cost-effectiveness ratio (ICER) of $71, 937/QALY, "treatment plus vaccination" was the most cost-effective HSIL management strategy using the willingness-to-pay threshold of 100, 000/QALY. We found that population-level EVPI for conducting future clinical research evaluating HSIL management approaches was US$12 million (range $6–$20 million). The EVPPI associated with adjuvant qHPV vaccination efficacy estimated in terms of hazards of decreasing HSIL recurrence was $0 implying that additional data from a future study evaluating efficacy of adjuvant qHPV vaccination will not change our policy conclusion that "treatment plus vaccination" was cost-effective. Both the ICER and EVPI were sensitive to HSIL treatment compliance. Conclusion: Post-treatment adjuvant qHPV vaccination in HIV-infected MSM aged 27 or above is likely to be cost-effective. Use of adjuvant qHPV vaccination could be considered as a potential strategy to reduce rising anal cancer burden among these high-risk individuals.